2017
DOI: 10.1186/s12864-017-4205-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrative testis transcriptome analysis reveals differentially expressed miRNAs and their mRNA targets during early puberty in Atlantic salmon

Abstract: BackgroundOur understanding of the molecular mechanisms implementing pubertal maturation of the testis in vertebrates is incomplete. This topic is relevant in Atlantic salmon aquaculture, since precocious male puberty negatively impacts animal welfare and growth. We hypothesize that certain miRNAs modulate mRNAs relevant for the initiation of puberty. To explore which miRNAs regulate mRNAs during initiation of puberty in salmon, we performed an integrated transcriptome analysis (miRNA and mRNA-seq) of salmon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…It is driven by distinct programs of gene regulation and cellular organization [ 22 ]. Previous studies have established functions for specific microRNAs in regulating reproduction [ 23 ]. However, only a few microRNAs and target genes involved in the development and reproduction of testis have been identified in mammals [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is driven by distinct programs of gene regulation and cellular organization [ 22 ]. Previous studies have established functions for specific microRNAs in regulating reproduction [ 23 ]. However, only a few microRNAs and target genes involved in the development and reproduction of testis have been identified in mammals [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established functions for specific microRNAs in regulating reproduction [ 23 ]. However, only a few microRNAs and target genes involved in the development and reproduction of testis have been identified in mammals [ 23 , 24 , 25 ]. Recently, it has been reported that a total of 61 DERs and 80 DEGs have been identified between cattleyak (cattle ♂ and yak ♀ ) and yak testes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, different miRs have been shown to have great influence on cell mitosis during mammalian gametogenesis (reviewed in [ 170 ]). In fish species, like salmon, not only new specific miRs have been linked to testis maturation, but also a functional conservation in vertebrates of known miRs involved in the transition into puberty have been suggested [ 171 ]. Different clinical studies have been explored the use of miRs as potential biomarkers for human male factor infertility [ 104 , 172 ].…”
Section: The Impact Of Vitamin K In Reproductionmentioning
confidence: 99%
“…The Dhh pathway seems highly involved in spermatogenesis as male mice with a Dhh null mutation are sterile (Bitgood et al 1996;Kroft et al 2001). Furthermore, the Dhh pathway has been shown to be significantly regulated during the salmon transition into puberty (Skaftnesmo et al 2017). Like gli1, myocyte enhancer factor 2A (mef2a) was also found differentially transcribed in the testes between the T10 group and control and was annotated with GO terms related to histone modification and similar to gli1, mef2a has been suggested as an important component of Dhh signaling (Wang et al 2006).…”
Section: A Deeper Look At the Cold Seawater Treatment Experimentsmentioning
confidence: 99%